A proposed cooperatives strategy for artisanal and small-scale gold mining sector in Zambia. (March 2021) - Banda, Webby; Chanda, Emmanuel K.
Abstract: The recent spate of gold discoveries in Zambia has necessitated the formulation of a coherent strategy to promote sustainable exploitation of gold for social-economic development. In this paper, a cooperatives strategy for artisanal and small-scale gold mining in Zambia is presented. The strategy exploits a state gold buying programme to promote three elements, namely, formalisation of the ASGM sector, poverty alleviation in communities hosting gold resources, and macroeconomic stability. To ensure the cooperatives thrive, a management structure was proposed and appraised based on three hypothetical small-scale gold mining projects. Additionally, tax policy was subsequently proposed to provide an enabling fiscal environment for the cooperatives. The proposed tax policy was assessed and compared to the current fiscal regime using the three small-scale mining projects. The current tax policy posted average effective tax rates of 52% – 55% and marginal effective tax rates of 43%– 45%. On the other hand, the proposed fiscal terms generated an average effective tax rate of 7% and marginal effective tax rates of 6%–7%. From these results, it can be concluded that the current fiscal regime imposes an excessively high tax burden on the artisanal and small-scale gold mining sector when compared to the proposed tax policy. Highlights: A cooperative strategy for Zambia's artisanal and small-scale gold mining sector is presented. Proposed strategy promotes formalisation of artisanal and small-scale mining. Additionally, the strategy promotes macroeconomic stability and poverty alleviation.